Prototipe Penerapan Knowledge Management System pada Sistem Informasi Kebudayaan Islam - Iis Afrianty; Ismail marzuki (UIN Sultan Syarif Kasim Riau, 2015)
This paper proposes a prototype of the Knowledge Management System (KMS) to provide the Islamic culture information in Riau Province by utilizing an interactive mapping zone. One of the causes of the fading Islamic culture in Indonesia is due to people tend to appreciate the cultures of other countries rather than cultures and artworks own country. Moreover, the Islamic culture information is still difficult to be found or is not accessible. Hence, it is highly required to develop a good system providing complete information to potential people who need information regarding the Islamic culture in Indonesia, especially in Riau Province. This information system can be developed by employing the KMS-based. It can organize, store, preserve the diversity of Islamic culture knowledge, and even foster the sharing knowledge practices interactively according to its mapping zone. Accordingly, this paper proposes a prototype of KMS-based for Islamic culture information in Riau Province.Keywords: Information Systems, Interactive Mapping zone, Islamic Culture, Knowledge Management System